Implementasi sistem pengelolaan dana Bantuan Operasional Sekolah (BOS) berdasarkan Permendikbud Nomor 6 Tahun 2021 di SD Inpres Nanas Kecamatan Wasile Selatan Kabupaten Halmahera Timur - Ester Arnitasya Djou; Wulan D. Kindangen (Yayasan Widyantara Nawasena Raharja, 2023)
School Operational Assistance Funds are funds provided by the government to schools. Financial management must be accounted for with transparency and accountability in accordance with BOS principles. This research aims to analyze in more depth the implementation of the School Operational Assistance (BOS) fund management system implemented by SD Inpres Nanas, South Wasile District, East Halmahera Regency Based on PERMENDIKBUD No. 6 of 2021 concerning Technical Guidelines for Managing School Operational Assistance Funds. The type of research used is qualitative with a descriptive approach. The results of research regarding the management of School Operational Assistance (BOS) funds at SD Inpres Nanas, South Wasile District regarding implementation and reporting have been carried out well in accordance with the Technical Instructions for PERMENDIKBUD No. 6 of 2021. However, planning has not been in accordance with the Technical Instructions for PERMENDIKBUD No. 6 of 2021. 2021 because the preparation of the school budget or RKAS has not been carried out in a transparent manner without involving parents and guardians of students, and the school has not published a joint decision regarding the preparation of the RKAS